The Community Fragmentation and Local Social Transformation due to Mining Activities in Raja Ampat, Papua : A Review from the Perspective of Structural Inequality - Irman Laia; Lorensius Apolinaris Ledo Wea; Christine F. Quenga (Master's Program in Sociology, Faculty of Social and Political Sciences, Universitas Negeri Surabaya, 2025)
This research examines the issue of mining in Papua. Papua, with its abundant natural resources, often becomes the primary target of mining exploitation. Despite the economic potential promised by the government, these mining activities frequently leave a legacy of environmental damage, community fragmentation, and profound social transformation. This case study highlights the impact of mining activities on local communities in Raja Ampat, Papua, an area known for its extraordinary underwater natural beauty. Using the perspective of structural inequality, this article analyzes how mining activities widen socioeconomic gaps, erode social cohesion, and fundamentally alter the structure of local society. Through Bourdieu's theory, it is explained that inequality in society occurs not only through economic control but also through the mastery of social, cultural, and symbolic capital. The study delves into the urgency of a more holistic and just development approach to prevent the negative impacts of mining and maintain socio-environmental sustainability in Papua.